Pengaruh Sistem Informasi Akuntansi, Sistem Pengendalian Internal dan Sistem Absensi terhadap Keakuratan Penggajian pada Kantor Camat di Kabupaten Buleleng - Maharani, Kadek Nanda; Purnamawati, I Gusti Ayu (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to determine the effect of accounting information systems, internal control systems, and attendance systems on the accuracy of payroll at the sub-district office in Buleleng Regency. This type of research is quantitative research. The population used was all employees at the sub-district office in Buleleng Regency. The sampling technique in this study used a purposive sampling method, with a sample of 135 people. The data source used is primary data obtained by distributing questionnaires to respondents. Data analysis in this study used descriptive analysis, data quality test, classical assumption test, and hypothesis testing with the help of SPSS version 23.0. The results showed that (1) the accounting information system had a positive and significant effect on the accuracy of payroll at the sub-district office in Buleleng Regency; (2) the internal control system has a positive and significant effect on the accuracy of payroll at the Head Office in Buleleng Regency; and (3) the attendance system has a positive and significant effect on the accuracy of the payroll at the sub-district office in Buleleng Regency